Social and Economic Rights Action Centre (SERAC) and the Centre for Economic and Social Rights (CESR) v Nigeria: two decades on – questioning the continued implementation gap (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
Nearly two decades after the landmark decision in Social and Economic Rights Action Centre (SERAC) and the Centre for Economic and Social Rights (CESR) v Nigeria, in which the African Commission on Human and Peoples’ Rights found that Nigeria had breached its obligations to protect, promote, and fulfil the rights of the Ogoni people in the country’s Niger Delta region, it is relevant to enquire how the decision has been implemented and whether it has significantly improved the situation of the Ogoni people. After the announcement of the Commission’s decision and the return to democratic rule in Nigeria, the general expectation was that Nigeria would without further delay implement the Commission’s recommendations. However, 20 years after the decision the Ogoni people are still demanding for their basic rights to be respected. This article, which mainly looks at the Commission’s decision from the perspective of the victims and through a socio-legal perspective, exposes this implementation gap. By doing so, it also points to the ineffectiveness of the monitoring mechanism of compliance with the Commission’s recommendations.
Keywords: African human rights system; environmental degradation; Ogoni case; Niger Delta; Ogoniland; implementation gap